Diagnostic re-evaluation of congenital hypothyroidism in Macedonia: predictors for transient or permanent hypothyroidism - Zdraveska, Nikolina; Zdravkovska, Maja; Anastasovska, Violeta; Shukarova Angelovska, Elena; Kocova Mirjana (Bioscientifica, 2018)
Background: Diagnostic re-evaluation is important for all patients with congenital hypothyroidism (CH) for determining the etiology and identifying transient CH cases. Our study is a first thyroxine therapy withdrawal study conducted in Macedonian CH patients for a diagnostic re-evaluation. We aimed to evaluate the etiology of CH, the prevalence of transient CH and identify predictive factors for distinguishing between permanent (PCH) and transient CH (TCH). Materials and methods: Patients with CH aged >3 years underwent a trial of treatment withdrawal for 4 weeks period. Thyroid function testing (TFT), ultrasound and Technetium-99m pertechnetate thyroid scan were performed thereafter. TCH was defined when TFT remained within normal limits for at least 6-month follow-up. PCH was diagnosed when TFT was abnormal and classified according the imaging findings. Results: 42 (55%) patients had PCH and 34 (45.0%) patients had TCH. Thyroid agenesia was the most prevalent form in the PCH group. Patients with TCH had lower initial thyroid-stimulating hormone (TSH) values (P < 0.0001); higher serum thyroxine levels (P = 0.0023) and lower mean doses of levothyroxine during treatment period (P < 0.0001) than patients with PCH. Initial TSH level <30.5 IU/mL and levothyroxine dose at 3 years of age <2.6 mg/kg/day were a significant predictive factors for TCH; sensitivity 92% and 100%, specificity 75.6% and 76%, respectively. Conclusion: TCH presents a significant portion of patients with CH. Initial TSH value and levothyroxine dose during treatment period has a predictive role in differentiating TCH from PCH. Earlier re-evaluation, between 2 and 3 years age might be considered in some patients requiring low doses of levothyroxine.
Keywords: congenital hypothyroidism; etiology; levothyroxine; transient